Respuesta :
Answer:
12
Step-by-step explanation:
so basically
(x^2+2)*(1-3x)=-3x^3+x^2-6x+2
now plug in -1
-3(-1)^3+(-1)^2-6(-1)+2=12
hope this helped :)
The correct value of (fg)(-1) is "12". A further solution of the given query is provided below.
Given functions are:
[tex]f(x) = x^2+2[/tex]
[tex]g(x) = 1-3x[/tex]
Now,
⇒ [tex](fg) = (x^2+2)(1-3x)[/tex]
By applying multiplication, we get
[tex]=x^2+2-3x^3-6x[/tex]
[tex]=-3x^3+x^2-6x+2[/tex]...(equation 1)
By substituting the value "-1" in place of "x" in equation 1, we get
⇒ [tex](fg)(-1) = -3(-1)^3+(-1)^2-(6)(-1)+2[/tex]
[tex]=-3(-1)+1+6+2[/tex]
[tex]=3+1+6+2[/tex]
[tex]=12[/tex]
Thus the right answer is (fg)(-1) = 12.
Learn more:
https://brainly.com/question/10057660
![Ver imagen Cricetus](https://us-static.z-dn.net/files/d6f/41d6712a1c4f2fd21914acc00288c74d.jpg)